PARENT’S ROLES OF CHILDREN PLAYING ACTIVITIES COGNITIVE DEVELOPMENT OF PRESCHOOL CHILDREN (5-6 YEARS) - Yusiana, Maria Anita; Herentina, Tabita (Jurnal Penelitian STIKES Kediri, 2012)
Stimulation is important in children's cognitive development. Parent’s play an important role in supporting playing activities of the children. The objective of this study was to analyze correlation betwen the parent’s roles of children playing activities with cognitive development of preschool children (5-6 years).  The design of this study was cross sectional. The population was all of parents and student at kediri baptis setia bakti kindergarten. The samples were 38 respondents taken by total sampling. The  independent variable was parent’s roles of  children playing activities. The dependent variable was cognitive development of  preschool children (5-6 years). The data’s were collected using questionnaires and observation list (checklist), then analyzed using spearman rho with significance level of α ≤ 0.05. The result showed p = 0,161, where p > α it mean that ha was refused and h0 was accepted. The conclusion of this study, there was no correlation betwen the parent’s roles of children playing activities with cognitive development of  preschool children (5-6 years) in kediri baptis setia bakti kindergarten.